Effects of regular yoga practice on neurological conditions and mental health - Karolina Zadrozna; Olga Wysokińska; Justyna Żyga; Anna Małek; Mateusz Fabiś; Bartłomiej Wójcik; Klara Iwaniszyn-Zapołoch (Kazimierz Wielki University, 2022)
Introduction Nowadays it is pointed out how important it is to take care of both mental and physical health. It is also undeniable that one affects the other and vice versa. That is why it is so important to nurture your body. Yoga as one of the physical activities has a proven effect on psychosomatic symptoms. Yoga is increasingly recommended mainly to relieve anxiety or stress. It brings great solace and even greater attentiveness. Lifestyle activities are increasingly considered an important component of treatment.   State of knowledge Medical conditions such as dementia, Parkinson's disease, headaches, PTSD, depression are mainly treated with drugs. Yoga, as a non-pharmacological treatment, alleviates psychological conditions, as it reduces stress, anxiety, depressive symptoms, and enhances attentiveness to one's self, self-control and a different perspective on traumatic situations.   Conclusions A review of the following works has shown the effects of yoga on mental health and common neurological conditions. With regular practice, it is possible to develop cognitive function, reduce the intensity and frequency of headaches. In Parkinson's disease, mindfulness exercises lead to an increase in muscle strength, a decrease in muscle tremors, and therefore improved rehabilitation. Most of the examples below mention a decrease in anxiety, stress, depressive symptoms and an increase in mindfulness, greater emotional and physical flexibility. The works cited point out that more in-depth research is needed to delve deeper into the effects of yoga on health.